Fatty acid binding protein 4 predicts left ventricular mass and longitudinal function in overweight and obese women. Issue 13 (18th April 2013) - Engeli, Stefan; Utz, Wolfgang; Haufe, Sven; Lamounier-Zepter, Valéria; Pofahl, Martin; Traber, Julius; Janke, Jürgen; Luft, Friedrich C; Boschmann, Michael; Schulz-Menger, Jeanette; Jordan, Jens
Abstract : Objective: To explore whether increased adipocyte-derived serum fatty acid binding protein 4 (FABP4) predisposes to cardiac remodelling and left ventricular dysfunction in human obesity. Design: Cross-sectional investigation. Setting: Academic clinical research centre. Patients: 108 overweight and obese non-diabetic women (body-mass index 33±5 kg/m²). Interventions: None. Main outcome measures: Relationship between serum FABP4 and abdominal adipose tissue quantified by MRI. Relationship between serum FABP4 and left ventricular morphology and function assessed by cardiac MRI. Results: FABP4 was independently associated with visceral abdominal adipose tissue (β=0.34, p<0.01) and subcutaneous abdominal adipose tissue (β=0.22, p<0.05). After stratification into serum FABP4 tertiles, left ventricular masses were 92±16 g, 86±13 g and 81±12 g in women with high, intermediate and low FABP4 concentrations (p<0.01), respectively. Longitudinal systolic function was reduced by 8% in women with intermediate and high versus low FABP4 concentrations (p<0.01), whereas ejection fraction did not differ among tertiles (p=0.5). In multivariate linear analysis FABP4 remained an independent predictor of left ventricular mass (β=0.17, p<0.05) and reduced longitudinal fractional shortening (β=0.21, p<0.05). Conclusions: In overweight and obese women, FABP4 showed an independent association with parameters of left ventricular remodelling.